Outpatient Financial Management Strategies in Increasing the Income of Dr. Sobirin Musi Rawas Hospital - Puspitasari, Jayanti; Yaniawati, Poppy; Mulyani, Kahar (Jurnal Indonesia Sosial Sains, 2026)
This study aims to analyze financial management strategies in the outpatient unit of Dr. Sobirin Musi Rawas Hospital in addressing the challenges of implementing the National Health Insurance (JKN) and increasing hospital revenue. The research employed a qualitative approach, with data collection techniques consisting of in-depth interviews, questionnaires, and analysis of financial documents. A SWOT analysis was applied to identify internal and external factors influencing financial performance and to determine the hospital’s strategic position. The results indicate that the hospital possesses several strengths, including competent human resources, relatively effective inter-unit coordination, utilization of the Hospital Management Information System (SIMRS), and a relatively high level of patient trust and outpatient visits. However, the study also identified several weaknesses, such as delays in BPJS claim disbursements, inefficient administrative processes, limited integration of digital systems, and the absence of regular financial evaluations. Opportunities available to the hospital arise from the sustainability of the JKN program, advances in digital technology, and potential collaboration with external parties. Meanwhile, threats include increasing competition from private healthcare facilities, rigid BPJS regulations, and cash flow instability caused by delayed claims. Based on the SWOT analysis, the hospital is positioned in Quadrant I, indicating that a growth strategy is the most appropriate approach to improve financial management and hospital revenue.